Workplace Deviant Behaviour in Response to Breach of Psychological Contract: The Mediation Effect of Moral Disengagement - Ms. Vanshika Jain; Mr. Chandra Shekhar Sharma (Ramanujan International Journal of Business and Research, 2020)
With the increased instances of deviant behaviours, there is a pressing need to explore its instigating variables. This article explores the influence of Breach of Psychological Contract (BPC) on two dimensions of workplace deviant behaviour namely, organisational deviance and interpersonal deviance through the mediating role of moral disengagement, a construct whose role has not been studied in the literature. The study is to explore the socio cognitive reaction of employees when the social exchange relationship between employer and employee is disturbed. It focuses on the fact that promises made to the employees matter. The data were collected from 248 employees working in private sector in India with at least one year of experience and analysed using Structural Equation Modelling and Mediation model developed by Baron and Kenny (1986) and Hayes (2008). Cross sectional study design is followed. The results show that Breach of Psychological Contract significantly affects both types of workplace deviant behaviour (organisational and interpersonal) with moral disengagement partially mediating the relationship. The conclusion drawn from the study will guide the managers to focus on maintaining psychological contracts for establishing a healthy social exchange relationship between employer and employee. It will help them to not go overboard with false promises and design their policies in such a manner that employee's psychological contracts are fulfilled. Use of moral disengagement as a mediator will highlight the importance of studying socio-cognitive reaction of employees to certain actions of the organisation.